The Jesuit relations and allied documents: travels and explorations of the Jesuit missionaries in New France, 1610-1791 - Thwaites, Reuben Gold (Burrows, 1896)
v. 1. Acadia, 1610-1613 -- v. 2. Acadia, 1612-1614 -- v. 3. Acadia, 1611-1616 -- v. 4. Acadia and Quebec, 1616-1629 -- v. 5. Quebec, 1632-1633 -- v. 6. Quebec, 1633-1634 -- v. 7. Quebec, Hurons, Cape Breton, 1634-1635 -- v. 8. Quebec, Hurons, Cape Breton, 1634-1636 -- v. 9. Quebec, 1636 -- v. 10. Hurons, 1636 -- v. 11. Hurons and Quebec, 1636-1637 -- v. 12. Quebec, 1637 -- v. 13. Hurons, 1637 -- v. 14. Hurons and Quebec, 1637-1638 -- v. 15. Hurons and Quebec, 1638-1639 -- v. 16. Quebec and Hurons, 1639 -- v. 17. Hurons and Three Rivers, 1639-1640 -- v. 18. Hurons and Quebec, 1640 -- v. 19. Quebec and Hurons, 1640 -- v. 20. Hurons and Quebec, 1640-1641 -- v. 21. Quebec and Hurons, 1641-1642 -- v. 22. Quebec and Hurons, 1642 -- v. 23. Hurons, Quebec, Iroquois, 1642-1643 -- v. 24. Lower Canada and Iroquois, 1642-1643 -- v. 25. Iroquois, Hurons, Quebec, 1642-1644 --